The Double Bind of Displacement: U.S. Sanctions, the Muslim Ban, and Experiences of Dislocation for Iranians Pursuing Higher Education in the United States. Issue 3 (22nd March 2022) - Ranjbar, A. Marie
Abstract : In this article, I examine the material and affective impacts of U.S. foreign policy on Iranians pursuing higher education in the United States. I argue that punitive policies against Iran have created a double bind for Iranians, in which in situ displacement becomes a defining feature of life. I first situate the concept of in situ displacement within feminist theories of displacement and geopolitics to describe the incremental loss of economic, political, and social security in daily life, while remaining in place. Second, I analyze how U.S. foreign policy toward Iran results in in situ displacement for Iranian students, including feeling stuck in place due to restrictive visas, long delays in green card processing, and fears that they cannot reenter the United States if they travel to Iran. Drawing on key informant interviews and the analysis of U.S. regulatory documents, I demonstrate how the Trump administration's Muslim ban laid bare different modalities of violence produced through four decades of punitive policies toward Iran. My analysis of sanctions, alongside the Muslim ban, reveals a complicated patchwork of regulations that are intended to target the Iranian state, yet these policies can have devastating consequences for Iranian students. I conclude with how these cases, although diverse, offer insight into how tensions between the United States and Iran result in multiple and varied forms of displacement, from the scale of the home to the geopolitical.